Perceptions des professionnels de la santé quant aux besoins oncologiques pédiatriques offerts en français à domicile : étude descriptive qualitative - Chartrand, Julie; Jibb, Lindsay; Grandmont, Camille; Hardy-Bélanger, Élisabeth; Cheng, Sara; Balasa, Rebecca; Johnston, Donna (Revue canadienne de soins infirmers en oncologie, 2022)

Does end-of-life care differ for Anglophones and Francophones? A retrospective cohort study of decedents in Ontario, Canada - Guerin, Ewa; Batista, Ricardo; Hsu, Amy. T.; Gratton, Valérie; Chalifoux, Mathieu; Prud’homme, Denis; Tanuseputro, Peter (Journal of Palliative Medicine, 2018)
Background: Approximately half of decedents in Ontario, Canada, receive some palliative care, but little is known about the influence of language on the nature of these services. Objective: To examine differences between English- and French-speaking residents of Ontario in end-of-life care and outcomes (e.g., health care costs and location of death). Design: A retrospective cohort study using multiple linked databases. Setting/Subjects: A population-based cohort of decedents in Ontario (2010–2013) who were living in long-term care institutions (i.e., nursing homes) or receiving home care before death (N = 25,759). Data from two regions with higher representations of Francophones were examined, with the final distribution by primary language being 75% Anglophone, 18% Francophone, and 7% other languages. Results: Compared with Anglophones, Francophones were more frequent users of long-term care (47.6% vs. 37.1%) and less frequent users of home care (71.3% vs. 76.3%). In adjusted models, the number of days spent in hospital in the last 90 days of life was similar between Anglophones and Francophones, although the odds of dying in hospital were significantly higher among the latter. The mean total health care cost in the last year of life was slightly lower among French ($62,085) compared with English ($63,814) speakers. Conclusions: There are statistically significant differences in end-of-life outcomes between linguistic groups in Ontario, namely more institutionalization in long-term care, less home care use and more deaths in-hospital among Francophones (adjusted). Future research is needed to examine the cause of these differences. Strategies to ensure equitable access to quality end-of-life care are required.

Le vieillissement francophone en contexte minoritaire. Défis et opportunités - Siméon, Frantz; Couturier, Yves (Reflets, 2021)